Use of National Consumer Survey Data to Explore Perceptions of Complementary and Alternative Medicine - Alina Cernasev; Basma Goma; Keri Hager; Lawrence Brown; Jon Schommer (University of Minnesota Libraries Publishing, 2020)
Background: Although Complementary and Alternative Medicine (CAM) has been the standard of therapy in Asia for centuries, it started receiving more attention in the U.S. in the last three decades. Objectives: The primary study objective was to explore individuals' perspectives of CAM. A secondary objective was to describe individuals' perceptions of pharmacists' roles in facilitating their use of these services and products. Methods: Data were obtained from the 2015 and 2016 National Consumer Surveys on the Medication Experience and Pharmacist Roles. Data were collected from adults residing in the United States via on-line, self-administered surveys coordinated by Qualtrics Panels between April 28 and June 22, 2015 (n = 26,173) and between March 14 and 30, 2016 (n = 10,500). This study focused on written comments made in the surveys with Content Conventional Analysis applied to the text.   Four researchers were trained to conduct coding to assess inter-judge reliability. The four judges had a high level of agreement which was greater than 0.95 for category type. Results: Out of a total of 36,673 respondents, 80% (29,426) submitted written comments at the end of the survey. Of these, 2,178 comments were about medications or health and 170 (8%) comments specifically about CAM, of which 136 (6%) were usable for analysis. Conventional Content Analysis revealed five themes:1)The role of pharmaceutical and insurance companies in CAM; 2) Overuse of medications; 3) Physicians can play a role in creating a balance between prescription use and CAM; 4) Individuals believe that CAM is more effective than Western medicines and prefer it; 5) Individuals want pharmacists to have a better understanding of CAM. The results of this study reveal individuals' opinions regarding how they want CAM to be considered in their interactions with their healthcare team. Conclusion: Emergent themes suggest that individuals are interested in receiving more professionals' healthcare to become more knowledgeable about CAM.   Article Type: Original Research